Rationality is not consistency - Daniele Caliari (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
We challenge the standard definition of economic rationality as consistency by making use of a novel distinction between axioms of decision theory: consistency and preference axioms. We argue that this distinction has been overlooked by the literature and, as a result, evidence that consistency is a proxy of decision-making ability is often based on incorrect identification strategies. We conduct an experiment to investigate the factors that drive violations of consistency alone. While we find no evidence that consistency axioms are a proxy of decisionmaking ability, we provide suggestive evidence that some preference axioms are, confirming their potential role as confounding factors. Overall, our experimental evidence raises doubts about the choice of language that equates consistency with rationality in economics.
Keywords: D00; D90; D91; 330; Decision Theory; Experimental Design; Consistency; Rationality